High‐Density Lignin‐Derived Carbon Nanofiber Supercapacitors with Enhanced Volumetric Energy Density. Issue 17 (20th May 2021) - Hérou, Servann; Bailey, Josh J; Kok, Matt; Schlee, Philipp; Jervis, Rhodri; Brett, Dan J. L.; Shearing, Paul R.; Ribadeneyra, Maria Crespo; Titirici, Magdalena
Abstract: Supercapacitors are increasingly used in short‐distance electric transportation due to their long lifetime (≈15 years) and fast charging capability (>10 A g −1 ). To improve their market penetration, while minimizing onboard weight and maximizing space‐efficiency, materials costs must be reduced (<10 $ kg −1 ) and the volumetric energy‐density increased (>8 Wh L −1 ). Carbon nanofibers display good gravimetric capacitance, yet their marketability is hindered by their low density (0.05–0.1 g cm −3 ). Here, the authors increase the packing density of low‐cost, free‐standing carbon nanofiber mats (from 0.1 to 0.6 g cm −3 ) through uniaxial compression. X‐ray computed tomography reveals that densification occurs by reducing the inter‐fiber pore size (from 1–5 µm to 0.2–0.5 µm), which are not involved in double‐layer capacitance. The improved packing density is directly proportional to the volumetric performances of the device, which reaches a volumetric capacitance of 130 F cm −3 and energy density of 6 Wh L −1 at 0.1 A g −1 using a loading of 3 mg cm −2 . The results outperform most commercial and lab‐scale porous carbons synthesized from bioresources (50–100 F cm −3, 1–3 Wh L −1 using 10 mg cm −2 ) and contribute to the scalable design of sustainable electrodes with minimal 'dead volume' for efficient supercapacitors. Abstract : This paper presents an innovative method to control the microstructure and the density of bio‐based carbon electrodes for energy‐storage applications. Lignin‐derived nanofibers are first electrospun and then compressed uniaxially at 40 bars. After carbonization, the free‐standing porous carbon materials exhibit densities above 0.6 g cm −3 and low void volume, leading to high volumetric capacitance of 130 F g −3 in supercapacitors.